In Vitro Evaluation of Weizmannia coagulans Strain LMG S-31876 Isolated from Fermented Rice for Potential Probiotic Properties, Safety Assessment and Technological Properties - Madapati Sreenadh; Kallur Ranjith Kumar; Soumitra Nath (Life, 2022)
Bacillus coagulans, which has been taxonomically reclassified as Weizmannia coagulans, has been the focus of research due to its wide distribution in fermented foods, probiotic properties, and tolerance to extreme environments. The purpose of this study was to characterise putative probiotic bacteria in a fermented rice sample, followed by an in vitro screening of presumptive probiotic properties and a safety assessment to ensure their safety for human consumption. The predominant isolate was Gram-positive, rod-shaped, catalase-positive, spore-forming, motile, and facultatively anaerobic. The biochemical test and 16S rDNA sequencing identify the isolate as Weizmannia coagulans strain LMG S-31876. The strain showed significant viability in acidic gastric juice, pancreatin, and bile. The strain showed tolerance to 5% NaCl, and a low-to-moderate percentage of hydrophobicity and auto-aggregation was recorded. It met all safety criteria, including haemolytic activity, DNase activity, antibiotic sensitivity, and growth inhibition of other bacteria. Evaluation of its technological properties showed positive results for amylolytic and lipolytic activities; however, negative results were obtained for proteolytic activity. It could be concluded from the gathered data that W. coagulans strain LMG S-31876 isolated from fermented rice, might serve as a potential functional probiotic food. However, extended follow-up durations and larger-scale trials by assessing the therapeutic effects in managing various clinical gastrointestinal conditions are required to warranty such effects.